The “Customer” is Not Always Right: Third-Party Sexual Harassment in Libraries - Lieu, Angela; Allard, Danielle; Oliphant, Tami (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2019)
Third party sexual harassment is often experienced by frontline library workers and is perpetuated by the very patrons they endeavour to support. This paper reports on the results of an environmental scan designed to delineate the interdisciplinary scope of third-party sexual harassment, to describe methods and methodologies used to understand this issue from a variety of disciplinary perspectives, and to inform future research in Library and Information Studies on this understudied, but critically important topic.